International Seabed Regime in Southeast Asia: The Lack of ASEAN Member States’ Role in Seabed Mining - Arif Satrio Nugroho; Ika Riswanti Putranti (Indonesian Perspective, 2018)
International Seabed Authority (ISA) as a part of implementation of UNCLOS Part XI has main objective is to foster healthy economic development especially for developing states and to minimize the negative environmental impacts derived from activities in the area. Although ISA had facilitated states to provide legal procedure to establish seabed explorations, the role of developing states are still lacking. For instance, the role of ASEAN member states are still minimum though some of its states rely on maritime resources such as Indonesia and Philippines. This paper argues that there are two main factors that cause minimum roles of ASEAN states in the development of seabed mining; lack of awareness of government officials, academics and its people in development of law of sea, mainly in seabed mining matters and the excessive cost and high technology requirements to explore and later to exploit seabed materials. To overcome the issue, ASEAN states should increase its stakeholder awareness in law of sea progress and the importance of seabed mining. In addition, ASEAN states could wait the Enterprise as an economic arm of The Authority to come into account to facilitate developing states in seabed exploitation for commercial value. In order to overcome environmental issue regarding seabed mining, ASEAN should maximize its own body of institution which already been built.Keywords: International Seabed Authority, seabed mining, ASEAN